Powder for forming PJ9 small magnetic core and preparation process of powder

By preparing a special powder, combined with the mixing and wet conditioning process of vibration mill grinding and double-axis mixed humidification mixer, the problem of low strength of the blank after the PJ9 small magnetic core is solved, and the efficient molding and blanking of the powder are achieved Increased strength of the parts.

CN119495503APending Publication Date: 2025-02-21WUXI SPINEL MAGNETICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311048832.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When the existing powders are produced in small PJ9 magnetic cores, the formed blanks are low in strength, cannot be transported and grasped, and cannot be effectively formed.

Method used

Prepare a special powder containing 53-54% iron oxide, 35-40% manganese tetraoxide, 8-12% zinc oxide, 0.03-0.06% glycerol, 0.01-0.05% ethylene glycol, 0.01-0.05% Carboxymethyl cellulose and 3-5% other auxiliary materials are mixed and adjusted by a vibration mill, mixed and adjusted by a double-shaft mixer, and glycerol, ethylene glycol and carboxymethyl cellulose are added during standstill.

Benefits of technology

It improves the molding plasticity of powder, enhances the strength of the blank after forming the PJ9 small magnetic core, solves the problem of the blank being unable to transport and grasp, and meets the molding and pressing requirements of the PJ9 small magnetic core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495503A_ABST
    Figure CN119495503A_ABST
Patent Text Reader

Abstract

The invention discloses a powder material for forming a PJ9 small magnetic core and a preparation process of the powder material, and relates to the technical field of manganese zinc ferrite magnetic core production. The powder material is prepared from the following raw materials in percentage by weight: 53-54% of ferric oxide, 35-40% of manganous-manganic oxide, 8-12% of zinc oxide, 0.03-0.06% of glycerol, 0.01-0.05% of ethylene glycol, 0.01-0.05% of carboxymethyl cellulose and 3-5% of other auxiliary materials, and the auxiliary materials comprise but not limited to a plasticizer, nickel oxide, copper oxide and the balance of unavoidable impurities. According to the powder used for forming the PJ9 small magnetic core and the preparation process of the powder, when the powder is used for a manganese-zinc soft magnetic ferrite forming procedure and PJ9 small product production, special powder is prepared for forming, a trace amount of plasticizer and 0.05% of glycerinum, 0.03% of ethylene glycol and 0.03% of carboxymethyl cellulose are added by weight, so that the humidified powder is easy to form, manpower is saved, the production efficiency is improved, and the production cost is reduced. The quality is improved, the production requirement is met, and the problems that after the PJ9 small magnetic core is formed, the blank strength is low, and forming cannot be achieved are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of manganese-zinc ferrite core production, in particular to a powder material used for molding a PJ9 small magnetic core and a preparation process thereof. Background Art

[0002] Manganese zinc soft ferrite is a kind of soft ferrite, usually called ferrite core, with spinel structure, made of iron, manganese, zinc oxides and their salts, using ceramic technology. It has high initial magnetic permeability and is generally used in the frequency range of 1 kHz to 10 MHz. It can be used to make inductors, transformers, filter cores, magnetic heads and antenna rods.

[0003] In the production process of manganese-zinc soft ferrite products, molding is a very important process. Different powders used in molding have a great influence on the quality of the blanks after molding.

[0004] When using existing powder materials to produce PJ9 products, since PJ9 products are very small and complex in shape, and the thickness of the edge is only 0.3mm, the formability of the powder materials is very high. If conventional powder materials are used, the blanks after forming will have no strength and will break at the slightest touch of the hand. They cannot be transported or grasped, and cannot be formed at all. How to improve the forming plasticity of the powder materials to adapt to the forming and pressing of small magnetic cores is a topic we need to study.

[0005] Therefore, it is urgent to improve this shortcoming. The present invention studies and improves the existing structure and shortcomings, and provides a powder material and a preparation process for PJ9 small magnetic core molding. Summary of the invention

[0006] The object of the present invention is to provide a powder material used for forming a PJ9 small magnetic core and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a powder material used for forming a PJ9 small magnetic core, the powder material is made of the following raw materials in weight percentage: 53-54% iron oxide, 35-40% manganese tetraoxide, 8-12% zinc oxide, 0.03-0.06% glycerol, 0.01-0.05% ethylene glycol, 0.01-0.05% carboxymethyl cellulose, 3-5% other auxiliary materials, the auxiliary materials include but are not limited to plasticizers, nickel oxide, copper oxide, and the rest are inevitable impurities.

[0008] The present invention also provides the following technical solution: a preparation process of powder used for forming a PJ9 small magnetic core, comprising the following steps:

[0009] S1. Raw material weighing:

[0010] Weighing iron oxide, manganese tetraoxide, zinc oxide, glycerol, ethylene glycol and carboxymethyl cellulose in order according to the weight percentage of the raw material components, and weighing other auxiliary materials;

[0011] S2. Raw material grinding:

[0012] The weighted solid raw materials are put into a vibration mill, and the vibration mill is used to grind each solid raw material into powder particles in turn to obtain a powdered raw material;

[0013] S3, mixed humidity control:

[0014] The powdered iron oxide, powdered manganese tetraoxide, and powdered zinc oxide prepared in S2 are fed into a double-shaft mixing and humidifying mixer, and the raw materials are mixed evenly by the double-shaft mixing and humidifying mixer, and the powder is humidified during the mixing and stirring process, and an appropriate amount of plasticizer is added;

[0015] S4, Mixing and Standing:

[0016] Add the weighted glycerin, ethylene glycol and carboxymethyl cellulose to the humidified powder, start the double-shaft mixing humidifying mixer to continue mixing, and let the powder stand after mixing to allow the above three additives to evenly penetrate into the powder particles.

[0017] Furthermore, in step S1, the weight percentages of the raw materials obtained by weighing are: 53.5% iron oxide, 37.5% manganese tetraoxide, 10% zinc oxide, 0.05% glycerol, 0.03% ethylene glycol, 0.03% carboxymethyl cellulose, 3% plasticizer, 0.5% nickel oxide and 0.5% copper oxide.

[0018] Furthermore, in step S2, the processing time of each solid raw material in the vibration mill is 25 minutes.

[0019] Furthermore, in step S2, the obtained powdered raw material needs to be screened using a sieve, and the particle size of the raw material powder obtained after screening is in the range of 1-1.5 μm.

[0020] Furthermore, in step S3, the operation time of powder mixing and the operation time of powder moisture adjustment overlap, and the duration of powder mixing is 15 minutes, and the duration of powder moisture adjustment is 10 minutes.

[0021] Furthermore, in step S3, the starting time of the powder moisture adjustment is when the powder mixing is performed for 5 minutes, and the ending time of the powder moisture adjustment is the same as the ending time of the powder mixing.

[0022] Furthermore, in step S3, the powder humidity adjustment temperature is controlled at 20-30° C. until the moisture content of the powder rises to 2-5%, and the moisture content is measured by random sampling using a powder moisture detector.

[0023] Furthermore, in step S4, the duration of powder mixing is 8 minutes, and the stirring speed is controlled at 100-200 rpm.

[0024] Furthermore, in step S4, the powder is left to stand for 24 hours, and the standing temperature is controlled at 25-30°C.

[0025] The invention provides a powder material and a preparation process for molding a PJ9 small magnetic core, which have the following beneficial effects: the method is used in the molding process of manganese-zinc soft ferrite. When producing a small PJ9 product, a special powder material is prepared for molding. By adding a trace amount of plasticizer and adding 0.05% glycerol + 0.03% ethylene glycol + 0.03% carboxymethyl cellulose (CMC) in a weight ratio, the powder material after moisture adjustment is easy to mold, which saves manpower, improves quality, meets production requirements, and solves many problems of low strength of the PJ9 small magnetic core after molding and inability to mold. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A front view schematic diagram of a PJ9 small magnetic core of the present invention showing a powder material used for forming a PJ9 small magnetic core and a preparation process thereof;

[0027] Figure 2 This is a schematic diagram of the back side of a PJ9 small magnetic core of the present invention, showing the powder material used for molding the PJ9 small magnetic core and its preparation process. DETAILED DESCRIPTION

[0028] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0029] like Figure 1-Figure 2 As shown, a powder material used for forming a PJ9 small magnetic core is made of the following raw materials in weight percentage: 53-54% iron oxide, 35-40% manganese tetraoxide, 8-12% zinc oxide, 0.03-0.06% glycerol, 0.01-0.05% ethylene glycol, 0.01-0.05% carboxymethyl cellulose, 3-5% other auxiliary materials, the auxiliary materials include but are not limited to plasticizers, nickel oxide, copper oxide, and the rest are unavoidable impurities.

[0030] A preparation process of powder used for forming a PJ9 small magnetic core comprises the following steps:

[0031] S1. Raw material weighing:

[0032] Weighing iron oxide, manganese tetraoxide, zinc oxide, glycerol, ethylene glycol and carboxymethyl cellulose in order according to the weight percentage of the raw material components, and weighing other auxiliary materials;

[0033] S2. Raw material grinding:

[0034] The weighted solid raw materials are put into a vibration mill, and the vibration mill is used to grind each solid raw material into powder particles in turn to obtain a powdered raw material;

[0035] S3, mixed humidity control:

[0036] The powdered iron oxide, powdered manganese tetraoxide, and powdered zinc oxide prepared in S2 are fed into a double-shaft mixing and humidifying mixer, and the raw materials are mixed evenly by the double-shaft mixing and humidifying mixer, and the powder is humidified during the mixing and stirring process, and an appropriate amount of plasticizer is added;

[0037] S4, Mixing and Standing:

[0038] Add the weighted glycerin, ethylene glycol and carboxymethyl cellulose to the humidified powder, start the double-shaft mixing humidifying mixer to continue mixing, and let the powder stand after mixing to allow the above three additives to evenly penetrate into the powder particles.

[0039] In step S1, the weight percentages of the raw materials obtained by weighing are: 53.5% iron oxide, 37.5% manganese tetraoxide, 10% zinc oxide, 0.05% glycerol, 0.03% ethylene glycol, 0.03% carboxymethyl cellulose, 3% plasticizer, 0.5% nickel oxide and 0.5% copper oxide; by strictly controlling the weight ratio of each raw material component, the purpose of accurately preparing the powder is achieved, which is conducive to ensuring the performance of the prepared powder.

[0040] In step S2, the processing time of each solid raw material in the vibration mill is 25 minutes; by processing the solid raw materials separately, it is ensured that each raw material can be ground thoroughly by the vibration mill to facilitate subsequent operations such as mixing and humidity adjustment.

[0041] In step S2, the obtained powdered raw material needs to be screened using a sieve, and the particle size range of the raw material powder obtained after screening is 1-1.5μm; by using a sieve to screen the ground powdered raw material, the powder that is not thoroughly ground can be screened out and re-put into the vibration mill for processing until the powder is screened to be qualified, ensuring that the powder is ground to the target size.

[0042] In step S3, the operation time of powder mixing overlaps with the operation time of powder moistening, and the duration of powder mixing is 15 minutes, and the duration of powder moistening is 10 minutes; starting the powder mixing first to pre-mix the three raw materials, and then moistening, can avoid the problem of uneven final powder mixing due to the increased difficulty of powder mixing after moistening.

[0043] In step S3, the starting time of powder moistening is 5 minutes after the powder mixing, and the ending time of powder moistening is the same as the ending time of powder mixing; by controlling the sequence and start time of powder mixing and powder moistening, it is beneficial to improve the powder mixing and lifting effect, thereby helping to improve the powder processing effect.

[0044] In step S3, the powder humidity control temperature is controlled at 20-30°C until the moisture content of the powder rises to 2-5%, and the moisture content is measured by random sampling using a powder moisture detector; by controlling the humidity control temperature, it is possible to avoid evaporation of water vapor due to excessively high temperature and poor combination of water and powder due to excessively low temperature, thereby promoting the humidity control of the powder. Random sampling detection can avoid moisture content detection errors caused by accidental errors, which is beneficial to ensuring that the moisture control of the powder is uniform and meets the target requirements.

[0045] In step S4, the duration of powder mixing is 8 minutes, and the stirring speed is controlled at 100-200 rpm; by controlling the duration of powder mixing and the stirring speed, the powder is ensured to be fully mixed, and the quality of the produced powder is improved, which is beneficial to the molding of PJ9 small magnetic cores and improves the quality of the produced PJ9 small magnetic cores.

[0046] In step S4, the powder is allowed to stand for 24 hours, and the standing temperature is controlled at 25-30°C; the powder is allowed to stand to ensure that glycerol, ethylene glycol and carboxymethyl cellulose are evenly infiltrated into the powder particles, thereby improving the quality of the powder. Furthermore, by controlling the standing temperature, the infiltration of glycerol, ethylene glycol and carboxymethyl cellulose is further promoted.

[0047] In summary, combined Figure 1-Figure 2 As shown, the working principle of the preparation process of the powder used for forming the PJ9 small magnetic core is as follows:

[0048] S1. Raw material weighing:

[0049] Weighing iron oxide, manganese tetraoxide, zinc oxide, glycerol, ethylene glycol and carboxymethyl cellulose in order according to the weight percentage of the raw material components, and weighing other auxiliary materials; the weight percentages of the raw materials obtained by weighing are: 53.5% iron oxide, 37.5% manganese tetraoxide, 10% zinc oxide, 0.05% glycerol, 0.03% ethylene glycol, 0.03% carboxymethyl cellulose, 3% plasticizer, 0.5% nickel oxide and 0.5% copper oxide;

[0050] S2. Raw material grinding:

[0051] The weighted solid raw materials are put into a vibration mill. The processing time of each solid raw material in the vibration mill is 25 minutes. The vibration mill is used to grind each solid raw material into powder particles in turn to obtain a powdered raw material. The obtained powdered raw material needs to be screened using a sieve. The particle size range of the raw material powder obtained after screening is 1-1.5 μm;

[0052] S3, mixed humidity control:

[0053] The powdered iron oxide, powdered manganese tetraoxide and powdered zinc oxide prepared in S2 are fed into a double-shaft mixing humidifying mixer, and the raw materials are mixed evenly by the double-shaft mixing humidifying mixer. During the mixing and mixing process, the powder is humidified, the operation time of the powder mixing overlaps with the operation time of the powder humidification, and the duration of the powder mixing is 15 minutes, and the duration of the powder humidification is 10 minutes. The starting time of the powder humidification is when the powder mixing is carried out for 5 minutes, and the end time of the powder humidification is the same as the end time of the powder mixing. At the same time, an appropriate amount of plasticizer is added, and the powder humidification temperature is controlled at 20-30°C until the moisture content of the powder rises to 2-5%, and the moisture content is measured by random sampling with a powder moisture detector;

[0054] S4, Mixing and Standing:

[0055] Add weighted glycerin, ethylene glycol and carboxymethyl cellulose to the humidified powder, start the double-shaft mixing humidifying mixer to continue mixing, the powder mixing lasts for 8 minutes, and the stirring speed is controlled at 100-200 rpm, and the powder is allowed to stand after mixing for 24 hours, and the standing temperature is controlled at 25-30°C, so that the above three additives can be evenly infiltrated into the powder particles.

[0056] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A powder material used for forming a PJ9 small magnetic core, characterized in that: The powder is made of the following raw materials in weight percentage: 53-54% iron oxide, 35-40% manganese tetraoxide, 8-12% zinc oxide, 0.03-0.06% glycerol, 0.01-0.05% ethylene glycol, 0.01-0.05% carboxymethyl cellulose, 3-5% other auxiliary materials, the auxiliary materials include but are not limited to plasticizers, nickel oxide, copper oxide, and the rest are inevitable impurities.

2. The process for preparing the powder used for forming the PJ9 small magnetic core according to claim 1, characterized in that: The following steps are involved: S1. Raw material weighing: Weighing iron oxide, manganese tetraoxide, zinc oxide, glycerol, ethylene glycol and carboxymethyl cellulose in order according to the weight percentage of the raw material components, and weighing other auxiliary materials; S2. Raw material grinding: The weighted solid raw materials are put into a vibration mill, and the vibration mill is used to grind each solid raw material into powder particles in turn to obtain a powdered raw material; S3, mixed humidity control: The powdered iron oxide, powdered manganese tetraoxide, and powdered zinc oxide prepared in S2 are fed into a double-shaft mixing and humidifying mixer, and the raw materials are mixed evenly by the double-shaft mixing and humidifying mixer, and the powder is humidified during the mixing and stirring process, and an appropriate amount of plasticizer is added; S4, Mixing and Standing: Add the weighted glycerin, ethylene glycol and carboxymethyl cellulose to the humidified powder, start the double-shaft mixing humidifying mixer to continue mixing, and let the powder stand after mixing to allow the above three additives to evenly penetrate into the powder particles.

3. The preparation process of the powder used for forming a PJ9 small magnetic core according to claim 2, characterized in that: In step S1, the weight percentages of the raw materials obtained by weighing are: 53.5% iron oxide, 37.5% manganese tetraoxide, 10% zinc oxide, 0.05% glycerol, 0.03% ethylene glycol, 0.03% carboxymethyl cellulose, 3% plasticizer, 0.5% nickel oxide and 0.5% copper oxide.

4. The process for preparing the powder used for forming the PJ9 small magnetic core according to claim 2, characterized in that: In step S2, the processing time of each solid raw material in the vibration mill is 25 minutes.

5. The preparation process of the powder used for forming the PJ9 small magnetic core according to claim 2, characterized in that: In the step S2, the obtained powdered raw material needs to be screened using a sieve, and the particle size of the raw material powder obtained after screening is in the range of 1-1.5 μm.

6. The process for preparing the powder used for forming the PJ9 small magnetic core according to claim 2, characterized in that: In step S3, the operation time of powder mixing and the operation time of powder moisture adjustment overlap, and the duration of powder mixing is 15 minutes, and the duration of powder moisture adjustment is 10 minutes.

7. The process for preparing powder used for forming a PJ9 small magnetic core according to claim 6, characterized in that: In the step S3, the starting time of the powder moisture adjustment is when the powder mixing is performed for 5 minutes, and the ending time of the powder moisture adjustment is the same as the ending time of the powder mixing.

8. The process for preparing powder used for forming a PJ9 small magnetic core according to claim 6, characterized in that: In step S3, the powder humidity adjustment temperature is controlled at 20-30° C. until the moisture content of the powder rises to 2-5%, and the moisture content is measured by random sampling using a powder moisture detector.

9. The process for preparing powder used for forming a PJ9 small magnetic core according to claim 2, characterized in that: In step S4, the powder mixing lasts for 8 minutes, and the stirring speed is controlled at 100-200 rpm.

10. The process for preparing powder used for forming a PJ9 small magnetic core according to claim 2, characterized in that: In step S4, the powder is left to stand for 24 hours, and the standing temperature is controlled at 25-30°C.